Global vacue chains: Brazil´s integration in international trade and the case of China - Scandiuzzi, Stephanie (2018)
This study aims at analyzing Brazil and China\'s integration in global value chains, from a legal perspective, by assessing their preferential trade agreements network and comparing to existing global value chain trade information and data. In order to do so, the following points are object of study: (i) the general theory of global value chains; (ii) the theory of preferential trade agreements under a global value chain perspective; (iii) the profile (choice of partners) and contents (legal provisions) of Brazil and China\'s preferential trade agreements network based on the Horn, Mavroidis and Sapir methodology; and (iv) Brazil and China\'s participation in global value chains based on literature and trade data. Results show that by employing the proxies of choice of partners and contents in comparison with literature and trade data on global value chain trade, Brazil\'s preferential trade agreement network is mostly limited to the Latin America region and can be understood as being shallow, and suggest that such network of trade agreements has not been conductive to value chain integration for Brazil. China\'s preferential trade agreement network is mostly focused on the Asian region and have relative depth, suggesting that China\'s agreements have to an extent assisted in the country\'s insertion in value chains.